Investigation of machining Ti-6Al-4V with graphene oxide nanofluids: Tool wear, cutting forces and cutting vibration. (January 2020) - Yi, Shuang; Li, Jinjin; Zhu, Jiahua; Wang, Xiangzhi; Mo, John; Ding, Songlin
Graphical abstract: Generally, tool/chip abrasion and build-up edge (BUE) were observed on the rake faces of the cutting tools, and the worn areas on the tools with the application of coolant with graphene oxide nanoparticles were smaller than the worn area of the tool when conventional coolant was applied, the materials abrasion area was smaller as well. Highlights: The cutting force decreased with the increase in GO concentration. Under the same cutting condition, the reduction could be up to 50.83% when GO nanofluids were used. Flank wear and the wear of rake face were reduced by 77.78% and 41.21%. The GO concentration of 0.3 wt.% showed the best performance on tool wear. Vibration was lower when lower feed rate and higher coolant pressure were applied. The GO nanofluids would make an effect on cutting vibration and the cutting vibration decreased as compared to that when CC coolant was used. Abstract: This paper investigated experimentally the machining of Ti-6A-4V with a new graphene based cutting fluid. Three different types of graphene oxide (GO) nanofluids with various GO concentrations were applied in a series of cutting experiments. Tool wear, cutting force and the vibration in turning titanium alloy with the new nanofluids as well as conventional coolant were analysed. The working mechanism and different cutting effects caused by the variation of GO concentration and coolant pressure were discussed. The results show that the cutting force was reduced by 50.83 % when GO nanofluids were used. The vibration in the turning Ti-6Al-4 V with GO nanofluids was significantly lower than that in using base fluids. While the Build-up-Edge (BUE) and adhered layers on the rake face were less than those formed in using conventional coolant, the reduction of flank wear was up to 44.1 %, 53.9 % and 71.3 % respectively when GO nanofluids with the concentration of 0.1 wt.% GO, 0.3 wt.% GO and 0.5 wt.% GO were applied.